Integrating leveling and InSAR networks for the monitoring of subsidence due to gas extraction - Odijk, Dennis (Wissner Verlag, 2005)
Although leveling is a very precise technique for geodetic deformation monitoring, it is quite expensive and time-consuming. InSAR is a relatively new technique for precise deformation monitoring and has some important advantages compared to leveling: the high spatial resolution of the data and the relatively low costs of the technique. In this article both techniques are considered for the estimation of subsidence due to gas extraction. Simulations demonstrate that although InSAR has the capability to provide sub-cm accuracy for this type of deformation monitoring, an integration with leveling is the best choice as long as InSAR is not at a fully reliable level.